Penerapan Teknik Bel Canto Dalam Menyanyikan Lagu The Prayer Oleh Andrea Bocelli dan Celine Dion Karya David Foster, Carole Bayer Sager, Alberto Testa, Tony Renis Pada Mahasiswa IAKN Tarutung Prodi Pendidikan Musik Gereja - Sebastian Situmeang; Eben Haezarni Telaumbanua; Testi Bazarni Zebua (LPPM Politeknik Pratama, 2024)
This research aims to determine the use of good Bel Canto singing techniques in singing, so that each note sounds beautiful, and is strong and round so that the message of the song can be conveyed. This research uses a qualitative descriptive method where researchers describe in the form of speech, writing and observations in the field. The work processes carried out for data collection are: observation, documentation, observations, videos and interviews. This research was carried out by collecting information through field research to obtain results which were processed into accurate data. The results of this research show that applying the Bel Canto technique in singing can improve singing ability. So it is necessary to practice and master good vocal techniques to be able to sing songs well.